PENGEMBANGAN LKPD ELEKTRONIK (E-LKPD) BERBASIS PROBLEM SOLVING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Edwianty, Widya; Herawati, Susi; Desfitri, Rita; Wahyuni, Yusri (De Fermat : Jurnal Pendidikan Matematika, 2026)
This study aims to develop a problem-solving-based Electronic Student Worksheet (E-LKPD) in the form of an APK file for Android users and to test its validity, practicality, and effectiveness in improving students’ mathematical problem-solving abilities. This study uses a research and development method with data collection instruments in the form of validation sheets, practicality questionnaires, and mathematical problem-solving ability test questions. Product validation was carried out by material experts and media experts. The results of the analysis show that the average validation in the material aspect is 98.66% with the category of "very valid" and in the media aspect is 84.61% with the category of "valid". The practicality test conducted at SMA Negeri 5 Padang obtained a percentage of 88.60% with the category of "very good". The results of the effectiveness test based on the N-Gain analysis showed an average value of 0.6594 or 65.94% with the category of "quite effective". Based on these results, it can be concluded that the developed problem-solving-based E-LKPD meets the criteria of being valid, practical, and quite effective so that it is feasible to be used as an alternative digital learning medium to support the improvement of students’ mathematical problem-solving abilities.